Urban Flash Floods: Global Strategies for Effective Mitigation - Rosmawati Mat Jihin,; Azmarini Ahmad Nazri,; Zanidah Ithnin,; Supa’at Zakaria@Jawahir,; Khairul Nizad Panior,; Mohd. Zulhairi Zulkipli, (International Journal of Integrated Engineering, 2025)
Flash flooding presents substantial risks to urban environments, carrying great financial, social, and environmental costs. Flash floods are difficult to manage and, therefore, require a comprehensive understanding of the underlying factors contributing to their occurrence and effective mitigation strategies. This research aims to develop a framework of requirements to efficiently mitigate urban flash floods by considering various aspects involved in a multi-disciplinary approach. This paper summarises previous research in flash floods, urban planning, and flood mitigation based on intensive studies. Moreover, to collect empirical data, a case study review has been conducted involving big cities within Malaysia and neighbouring countries. This research approach uses qualitative analysis to provide a better understanding of the intricate relationship between flash floods and their mitigation options. The findings of this research highlight the critical factors influencing the effectiveness of flood mitigation efforts in urban areas during flash flood events. This involves modifying urban infrastructure design, land-use planning, early warning systems, community preparedness, and policy frameworks. This study can have significant implications for urban planners, disaster management authorities, and the local communities involved in reducing the susceptibility to flash floods. The outcomes of this study provide a generic understanding for stakeholders involved in identifying and developing proactive measures that limit the impact of flash floods on urban environments. Ultimately, this research contributes significantly to the body of knowledge on urban flash flood mitigation and provides an integrated view across technology, policy, community engagement, and practice in influencing resilient communities for sustainable development in flood-prone areas.